2007
DOI: 10.1021/jp066995a
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Redispersion of Silver Clusters in Ag-MFI Zeolite as Investigated by Time-Resolved QXAFS and UV−Vis

Abstract: Dynamic structural changes of Ag in Ag-MFI upon H 2 reduction and subsequent reoxidation treatments were investigated by various characterization methods. Results of in situ time-resolved spectroscopies, UV-vis and quick XAFS, at 573 K show that Ag + ions at a cation-exchange site of preoxidized Ag-MFI are reduced by H 2 to a Ag 4 δ+ cluster. Protons on the zeolite (Brønsted acid sites) are also produced by the H 2 reduction of Ag-MFI as evidenced by IR measurements after D 2 adsorption. At higher reduction te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 44 publications
5
86
0
3
Order By: Relevance
“…However, there is still lack of data in the literature concerning application of silver-containing zeolites in the SCR of NO x . According to previous reports, dispersed silver species seem to be active catalytic centers of SCR of NO on Ag-MFI zeolites [18,19]. However, silver is not well dispersed in such materials, which contain silver in the form of various species, i.e., ions, nanoclusters, and metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 94%
“…However, there is still lack of data in the literature concerning application of silver-containing zeolites in the SCR of NO x . According to previous reports, dispersed silver species seem to be active catalytic centers of SCR of NO on Ag-MFI zeolites [18,19]. However, silver is not well dispersed in such materials, which contain silver in the form of various species, i.e., ions, nanoclusters, and metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 94%
“…Our group has paid attention to Ag clusters catalysts for automotive emission control 43)~45) and green organic syntheses 46)~52) . Based on the fact that the surface of metal particle with size below a few nanometer contains large number of low-coordinated metal atoms having high reactivity, we paid special emphasis on the catalysis of metallic Ag clusters with a size of subnanometer to a few nanometers.…”
Section: )~40)mentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24] We have been paying attention to cluster-specific catalysis by supported silver catalysts for environmental applications and have reported a series of studies on size-and supportspecific catalysis by silver clusters for the selective catalytic reduction of NOx with hydrocarbons for the removal of NOx emissions from diesel engine exhausts. [20][21][22] It has been shown that, of various silver catalysts, silver clusters on alumina constitute the best catalyst, with activity much higher than that of Pt/Al 2 O 3 catalyst. Fundamental studies showed that both the silver clusters and the acid-base sites on the support surface are responsible for the high activity of silver clusters on alumina.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental studies showed that both the silver clusters and the acid-base sites on the support surface are responsible for the high activity of silver clusters on alumina. [20][21][22] For this study we attempted an extension of the acid-base-assisted silver cluster catalysis to selective oxidation.…”
Section: Introductionmentioning
confidence: 99%